Human Adipose-Derived Stem Cells Impair Natural Killer Cell Function and Exhibit Low Susceptibility to Natural Killer-Mediated Lysis - Olga DelaRosa; Beatriz Sánchez-Correa; Sara Morgado; Cristina M. Ramírez; Borja del Río; Ramón Menta; Eleuterio Lombardo; Raquel Tarazona; Javier G. Casado (2011)
Human adipose-derived stem cells (hASCs) have been successfully used in treating numerous diseases. However, several aspects need to be considered, particularly in the context of allogeneic cell therapy. To better understand hASCs-host interactions, we studied the phenotype of hASCs and their modulatory effect on natural killer (NK) cells by using bone marrow-mesenchymal stem cells (hBM-MSCs) as a reference. The hASCs displayed a lower susceptibility to NK cell-mediated lysis and a lower expression of ligands for DNAM-1 when compared with hBM-MSCs. Moreover, here we demonstrated that hASCs and hBM-MSCs can modulate NK cells through the action of soluble factors such as indoleamine 2,3-dioxygenase. Altogether, these results suggest that for an adoptive cell therapy based on the transfer of allogeneic hASCs, the NK-hASCs crosstalk will not result in an immediate recognition of the transferred cells. Thus, hASCs may remain in the tissue long enough to balance the immune response before being cleared.